Study to Fabricate the Large Scale Buckypaper Based on Carbon Nanotubes - Tieu, Doanh Tu; Nguyen, My Khanh; Nguyen, Tham Thi Hong; Ngo, Thanh Vo Ke; Do, Quyet Huu (Communications in Physics, 2018)
Carbon nanotubes (CNTs) have attracted great attention because of their unique structural, electrical, mechanical and thermal properties. Then CNTs have potential application as electrode for batteries and supercapacitors, especially binder-free electrodes. The major challenge is to fabricate the large scale electrode with the uniform thickness, electrical property. The large scale CNTs buckypaper can be fabricated via vacuum filtration technique. The characteristics of CNT dispersion and buckypaper depend on variety of factor such as sonication power, sonication time, dispersant…. In this study, we investigate the multiwall carbon nanotubes (MW CNTs) in Isopropanol (IPA) solvent with different sonication conditions, membrane filter size for paper with areal density of 3 mg/cm2 with different sizes such as 4, 10, 20 cm in diameter and large scale of 30x30 cm2. It is observed that the dispersion of CNTs are good and the thickness, conductivity are uniform over whole sample for above sizes. We also can get the highest conductivity of buckypaper was 3.9x103 S/m in 30 mins. It is found that the higher sonication power and higher sonication time are better for buckypaper.